Ionospheric tomography for SWARM satellite orbit determination using single-frequency GNSS data - Prol, Fabricio S.; Pignalberi, Alessio; Smirnov, Artem; Pezzopane, Michael; Christovam, Ana L. [UNESP]; Selvan, Kannan; Hoque, Mainul; Kaasalainen, Sanna (Springer Nature, 2025)
Ionospheric tomography offers three-dimensional (3D) description of the electron density distribution, enabling the direct incorporation of electron density data into the slant total electron content (STEC) computation. As a result, STEC derived from tomography helps mitigate the ionospheric delay experienced in the line of sight between global navigation satellite systems (GNSS) and satellites positioned in low Earth orbits (LEO). Tomography can therefore be effectively employed to correct single-frequency GNSS observations and allow enhanced positioning of spaceborne platforms. We demonstrate the accuracy and performance of a global-scale ionospheric tomography method for determining satellite orbits, utilizing single-frequency GNSS measurements combined with a precise point positioning (PPP) algorithm. We compare the tomographic outcomes against orbit determination derived from the GRoup and PHase ionospheric correction (GRAPHIC) observable and based on an ionospheric climatological model. Near the peak of solar cycle 24, the overall accuracy achieved with tomography was around 3.8 m. notably, compared to the background climatological model, tomography demonstrated improvements ranging from 15 to 20%. The GRAPHIC method outperformed tomography, achieving an accuracy of 0.7 m, whereas we obtained around 7 m accuracy when no ionospheric model is employed. Although the developed ionospheric tomography has yet to match the precision of GRAPHIC, our results bring us relatively closer to this objective.
Keywords: Geomagnetic storm; GPS; GRAPHIC; Ionosphere; Low earth orbit; Swarm; Tomography